Prevalence of Helicobacter pylori diagnosed by endoscopy in children with gastrointestinal symptoms treated at a tertiary-level hospital in Lima, Peru - Muñoz-Urribarri, Ana (2025)
Helicobacter pylori - is an infection acquired in childhood, especially in countries with high prevalence such as Peru, however, the number of studies in this population is scarce, so the need to describe its prevalence and the need for treatment is evident. Objectives: To determine, through endoscopy and biopsy, the current prevalence of this infection in Peruvian children with digestive complaints who attend the Hospital Nacional Edgardo Rebagliati Martins. Materials and methods: A retrospective descriptive study was conducted with 242 patients aged 0 to 14 years, using the electronic medical records from the hospital system. Results: The prevalence of Helicobacter pylori was 27.2%. There were no characteristic symptoms in the positive versus negative- group. The most relevant endoscopic findings in the positive group were a high frequency of antral nodular gastritis (72.1% vs. 9.8%, p<0.001) and a lower prevalence of endoscopic esophagitis (13.1% vs. 23.6%, p<0.001). Otherwise, histopathological analysis revealed a higher presence of lymphoid follicles (24.5% vs. 4.5%, p<0.001), while chronic inflammation was lower (54% vs. 87.5%, p<0.001). Conclusions: It is concluded that the histopathological findings associated with positive Helicobacter pylori are characteristic in this group and prevalence of this bacteria in Peruvian children seen in a pediatric gastroenterology unit is apparently lower than similar previous studies. This highlights the need for further research to evaluate its relationship with the possibility of antimicrobial resistance and the rising of immune-mediated diseases.